Conflict Analysis in Luca Guadagnino's Call Me by Your Name - Tisca Amaranty Putri; Anton Sutandio (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
This article analyzes the conflicts experienced by the main character in the film Call Me by Your Name by Luca Guadagnino. Guadagnino is an Italian director known for films such as The Protagonist (1999), I am Love (2010), and Suspiria (2018). Call Me by Your Name (2017) is Guadagnino's film which discusses the issue of homosexuality set in a rural area in Lombardy, Italy in 1983. The analysis focuses on aspects of conflict because the issue of homosexuality is most clearly reflected through this aspect. The analysis is carried out to reveal the types of conflicts that occur, the causes of conflicts, conflict resolution, and how the film's cinematography helps visualize these conflicts. By using the formalism approach, it is concluded that there are two types of dominant conflict, namely social conflict and inner conflict. The main cause of the conflict is the character's inability to express his identity as a homosexual. The cinematographic aspect also helps conflict analysis through the visualization that is displayed.